2009
DOI: 10.1007/s00125-009-1461-1
|View full text |Cite
|
Sign up to set email alerts
|

Is islet autoimmunity related to insulin sensitivity or body weight in children of parents with type 1 diabetes?

Abstract: Aims/hypothesis It has been suggested that metabolic demand and insulin resistance play a role in the development of type 1 diabetes, including the onset of autoimmunity. The aim of the present study was to determine whether insulin demand is increased in children with islet autoantibodies. Methods BMI standard deviation score (BMI-SDS) was measured from 2 years of age in 1,650 prospectively followed children of mothers or fathers with type 1 diabetes, including 135 who developed persistent islet autoantibodie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 26 publications
3
19
0
Order By: Relevance
“…However, this requires confirmation in larger ongoing studies. The clamp test also allowed estimation of insulin sensitivity in FDRs and HVs, but in line with previous publications [29,30] it failed to detect differences in biological measures of insulin sensitivity according to clinical outcome.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…However, this requires confirmation in larger ongoing studies. The clamp test also allowed estimation of insulin sensitivity in FDRs and HVs, but in line with previous publications [29,30] it failed to detect differences in biological measures of insulin sensitivity according to clinical outcome.…”
Section: Discussionsupporting
confidence: 77%
“…The increase in concentration between time 0 and 30 min was determined for glucose (Δglucose 30 ) and C-peptide (ΔCP 30 ). The incremental response was defined as ΔCP 30 /Δglu-cose 30 as previously described [20]. The disposition index (DI) [21] was computed by multiplying ISI from the clamp with the OGTT-derived AUC 0-120 for C-peptide.…”
Section: Data Analysis and Statistical Testsmentioning
confidence: 99%
“…Finally, several studies indicate that in individuals at risk for the development of type 1 diabetes, insulin resistance is an independent risk factor for disease development (17,18,19,20), and in studies of identical twins the co-twin who goes on to develop type 1 diabetes is more insulin resistant than the twin who does not (21). However it is important to add that other studies question these findings, and hence the theory is controversial (22).…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic demand and insulin resistance have been suggested to be involved in the development of type 1 diabetes (Evertsen et al, 2009;Wilkin, 2009), but the evidence is not consistent across the studies. In 1650 prospectively followed children of mothers or fathers with type 1 diabetes (BABYDIAB cohort), islet autoantibodies-positive children were not insulin resistant (based on homeostasis model assessment of insulin resistance, HOMA-IR) and did not have increased BMI around and early after seroconversion (Winkler at al., 2009). In this study, of 777 children with HOMA-IR measurements, 84 developed islet antibodies during the study: analysis of HOMA-IR by age showed no significant difference between islet autoantibody-positive and islet autoantibody-negative children, with a tendency towards a lower HOMA-IR in the antibody-positive children compared with the antibody-negative children.…”
Section: Body Weight In Type 1 Diabetes Familiesmentioning
confidence: 99%